(untitled) (Medical Forum Monthly, 2024)
Objective: To assess administration of prophylactic use of corticosteroid 48 hours before elective caesarean section reduces neonatal respiratory morbidity in patients having previous caesarean sections and to see the relationship of neonatal respiratory morbidity with the gestational age at which caesarean section done. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Department of Gynaecology and Obstetrics Sughra Shafi Medical Complex Narowal from 1st January to 30th June 2018. Materials and Methods: This study included one hundred twenty consenting women. These women were scheduled for elective caesarean section and all had previous caesarean delivery, 60 randomized to Group A, who received I/M dexamethasone in 2 doses of 12mg/12 hours apart 48 hours before caesarean section and 60 to Group B who did not receive dexamethasone. Results: Fourteen infants were admitted to nursery, 4 newborns from the group A and 10 from the group B. Regarding indication of admission in group A only 1 (2%) baby developed RDS to 3(5%) in group B (p=0.0461).Besides 7 (12%) babies were admitted to nursery in group B due to TTN compared to 3 (5%) in Group A (p=0.0361).One baby in Group B expired .Admissions due to neonatal respiratory morbidity were more at 37 weeks than at 38 or 39 weeks. There were 9 at 37 weeks, 4 at 38 weeks and 1 at 39 weeks. Conclusion: Elective section should be delayed up to 39 weeks and if early term elective section is required, prophylactic dexamethasone 48 hours before caesarean section reduces neonatal respiratory morbidity and can be safely used.